The reality of teaching practices for Mathematic teachers in light of the STEM approach in Al Majmaah Governorate - Almtiri, Mneefah Qzai (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to reveal the reality of teaching practices for Mathematic teachers in light of the STEM approach. To achieve the objectives of the study, the researcher followed the quantitative approach represented by the descriptive survey approach, and used the questionnaire tool for all data divided into three axes. The study sample consisted of (57) female Mathematic teachers affiliated with the Majmaah Governorate Education Department for the academic year 1445/1446, 2024 AD. The study resulted in several results, including the reality of teaching practices for Mathematic teachers in light of the (STEM) approach from the point of view of Mathematic teachers in the Majmaah Education Department, which came in at a high level. The reality of teaching practices for Mathematic teachers in light of the (STEM) approach in the implementation phase came in first place. In terms of the reality of practice with a degree of (high), followed in second place by the reality of teaching practices for female Mathematic teachers in light of the (STEM) approach in the planning stage with a degree of use (high), then in third place is the reality of teaching practices for female Mathematic teachers in light of the (STEM) approach in the planning stage. Evaluation with a degree of use (high), and the results also revealed that there are no statistically significant differences between the average ranks of the sample members’ responses regarding the level of teaching practices for female Mathematic teachers in light of the (STEM) approach of the Majmaah Education Department, due to the variables of years of experience and the number of training courses. In light of the results, the researcher presented a set of recommendations and research proposals related to the subject of the study.
Keywords: teaching practices; Mathematic teachers; STEM entrance